Phase angle and World Health Organization criteria for the assessment of nutritional status in children with osteogenesis imperfecta - Vicky Nogueira Pileggi; Antonio Rodolpho Hakime Scalize; José Simon Camelo Junior
Abstract Objective: To compare the phase angle of patients with osteogenesis imperfecta treated at a tertiary university hospital with patients in a control group of healthy children, and to assess the nutritional status of these patients through the body mass index proposed by the World Health Organization. Methods: Cross-sectional study carried out in a university hospital that included seven patients with osteogenesis imperfecta and a control group of 17 healthy children of the same gender and age. Weight and height were measured and bioelectrical impedance was performed. Subsequently, the phase angle was calculated based on resistance and reactance values. Results: The phase angle of the group of children with osteogenesis imperfecta was significantly lower than that of the control group (p<0.05). The body mass index criterion for age of the World Health Organization showed no difference between groups. Conclusions: Children with osteogenesis imperfecta have a nutritional risk detected by the phase angle, which is a useful tool for nutritional screening. The calculation result could help in the diet therapy of patients with osteogenesis imperfecta.